Nature photography : a guide to better outdoor pictures - Osolinski, Stan (New Jersey : Prentice-Hall, 1981)
This book explore some of the ways in which believes it is possible to make that photographer in you a more sensitive naturalist and that naturalist in you a more capable photographer.
Chapter 1. Getting started -- Chapter 2. Understanding selectivity -- Chapter 3. The qualities of light -- Chapter 4. Equipment: guidelines to some basics -- Chapter 5. The nature of photography; the photography of nature.
Includes bibliographical references and index.
Keywords: PHOTOGRAPHY